Metabolome integrated with transcriptome, and genome analysis revealed higher accumulations of phytoalexins enhance resistance against Magnaporthe oryzae in new Zhefang rice variety diantun 506 - Owais Iqbal; Xingrun Yang; Ruoping Wang; Chun Wang; Dandan Li; Jiancheng Wen; Jiasheng Ding; Sauban Musa Jibril; Chengyun Li; Yi Wang (BMC Plant Biology)
Abstract Background Magnaporthe oryzae is one of the most devastating pathogens of rice, causing significant economic losses worldwide. Despite extensive studies on the M. oryzae-rice interaction, particularly focusing on the underlying resistance mechanisms, the molecular basis of rice resistance remains poorly understood. Results This study employed an integrated metabolomic, transcriptomic, and genomic approach to compare the response of Diantun susceptible (D502) and resistant (D506) rice lines to M. oryzae infection at 48 h post-inoculation. A total of 588 and 595 differentially accumulated metabolites (DAMs) were identified in D502 and D506, respectively. Notably, 55% of these metabolites exhibited similar expression patterns across both lines, while 9 DAMs displayed contrasting patterns at 48 h in response to pathogen infection. Pathway analysis revealed significant regulation of flavonoid, nucleotide derivatives, phenylpropanoid and polyketide, and vitamin biosynthesis pathways, with specific metabolites from these pathways potentially contributing to resistance in D506. KEGG enrichment analysis further identified key pathways in D506, including linoleic acid metabolism, plant hormone signal transduction, α-linolenic acid metabolism, and the pentose phosphate pathway. Network analysis based on DAMs and differentially expressed genes (DEGs) highlighted eight up-regulated metabolites and their key genes responsible for resistance, which are associated with flavonoid, tryptophan, and phytohormone, resulting in suppressed M. oryzae infection in D506. The content of sakuranetin was significantly higher, and the peak in expression of their key gene OMT-9 after M. oryzae infection at 48 h, lead to an increase in phytoalexin production in the D506 line. Subsequently, exonic non-synonymous single nucleotide polymorphisms (nsSNPs) within abscisic acid synthesis (NCED1) gene, identified through genome-wide analysis, were associated with amino acid substitutions potentially affecting protein function. This finding suggests that the ABA and their key genes are essential for the resistance in D506 against M. oryzae. Conclusion In last, we conclude that our findings underscore the power of integrating metabolomics, transcriptomics, and genomics to identify key metabolites and genes underlying resistance to M. oryzae. The insights gained from this study offer valuable resources for enhancing rice breeding strategies and improving disease management in agriculture.